INVESTIGATION OF THE SELF-ESTEEM LEVELS OF INTERNATIONAL STUDENTS - Şıhmehmet Yiğit; İbrahim Dalbudak (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi, 2019)
This study aimed to investigate the self-esteem levels of international students who study at different departments at Uşak University in terms of some socio-demographic backgrounds. The data were collected from 113 male and 35 female international students. In the data collection, two-part surveys applied to the participants. In the first part, a form that included items about socio-demographic backgrounds of the participants and in the second part, Cooper Smith Self - Esteem inventory short form which was consisted of 25 items used. The data were analyzed with SPSS 22 using Independent samples t-test, One Way Variance Analyze (ANOVA) and Tukey' s Hsd. As the results of this research, it was found that there were significant differences in the variable self-esteem according to gender, age, class, and sports situation of the participants. However, there were no significant differences according to nationality.